Hernies Ombilicales Étranglées De L’enfant Au Centre Hospitalier Régional De Ziguinchor (Sénégal) - Diouf Cheikh; Sow Omar; Diallo Ibrahima; Ndoye Ndeye Aby; Ngom Gabriel (European Scientific Journal, ESJ, 2017)
The umbilical hernia is a well-known pathology even though, its strangulation has been subject to much controversy. The aim of this work is to report our experience in the management of strangulated hernia of the child at the Ziguinchor regional hospital and to compare our results with those of the literature through a retrospective and descriptive study over a four years period. During the study period 24 patients with high male predominance were received. The mean age of the patients was 2.1 years. 45% of patients had a chronic cough. The average time for consultation was 27.6 hours. A notion of abdominal abrupt was found in 45% of the cases. The vast majority of patients arrived at the hospital during the dry season. Abdominal pain and vomiting were the main symptoms. An occlusive syndrome was present in about half of the patients. The diameter of the collar of the hernia varied between 1.5 and 2.5 cm and no intestinal necrosis was found during exploration. The surgery was simple in the majority of cases. Umbilical hernia is a reality in under-developed environment some factors promotes its complications.